Cocriação de valor em cursos corporativos: caso de uma instituição de ensino superior municipal - Lima, Wilker Silva (Universidade do Vale do Rio dos Sinos, 2024)
This study explores the dynamics of value co-creation in corporate education, focusing on how Higher Education Institutions (HEIs) can align their corporate courses with the often complex needs of organizations. Based on the premise that competitiveness and the demand for professional qualification drive HEIs to reshape their educational offerings, this work investigates value co-creation as a collaborative process among stakeholders, including students, teachers, and corporate partners. The objective was to analyze how value co-creation in a corporate education course at a public Municipal Higher Education Institution influences the learning experience of participants and meets market expectations. To achieve this objective, a qualitative methodology was adopted, using semi-structured interviews with students, coordinators, and teachers involved in the course. The results indicate that value co-creation in the educational context is influenced by the interaction among course participants, the adaptation of content to students' practical needs, and the ability to apply the acquired knowledge in real work situations. The analysis revealed that collaborative and adaptive practices are crucial for creating an educational experience that not only conveys knowledge but also builds competencies relevant to the market.
Keywords: Educação corporativa; Experiência de aprendizagem; Adaptação; Corporate education; Learning experience; Adaptation; ACCNPQ::Ciências Sociais Aplicadas::Administração